2008
DOI: 10.1074/jbc.m707951200
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Selenocysteine Machinery and Selenoproteome Gene Expression in Mouse Brain Identifies Neurons as Key Functional Sites of Selenium in Mammals

Abstract: Although dietary selenium (Se) deficiency results in phenotypes associated with selenoprotein depletion in various organs, the brain is protected from Se loss. To address the basis for the critical role of Se in brain function, we carried out comparative gene expression analyses for the complete selenoproteome and associated biosynthetic factors. Using the Allen Brain Atlas, we evaluated 159 regions of adult mouse brain and provided experimental analyses of selected selenoproteins. All 24 selenoprotein mRNAs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
128
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(138 citation statements)
references
References 62 publications
7
128
1
2
Order By: Relevance
“…In the present study, higher expression of this gene was observed in brain of fish fed diets with high substitution levels and thus lower Se contents, which could indicate an up-regulation in the biosynthesis of new SEP. Although in mammals transcriptional changes in the brain in response to Se are rare (65) , some studies in fish brain have found differential expression when Se was supplemented to the diet. For instance, Benner et al (66) found increased expression of secp43 in brain with increased dietary Se supplementation in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, higher expression of this gene was observed in brain of fish fed diets with high substitution levels and thus lower Se contents, which could indicate an up-regulation in the biosynthesis of new SEP. Although in mammals transcriptional changes in the brain in response to Se are rare (65) , some studies in fish brain have found differential expression when Se was supplemented to the diet. For instance, Benner et al (66) found increased expression of secp43 in brain with increased dietary Se supplementation in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…Sepp1 is expressed within the brain by astrocytes and likely by other cells (39,40). The Sepp1 receptor apoER2 is present on neurons (41), so it is possible that Sepp1 functions to maintain appropriate distribution of selenium among cells in the brain as it does among tissues in the body (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, because of the predicted location of SelM in the endoplasmic reticulum and recent studies indicating that another ER-localized selenoprotein, selenoprotein N, is required for ryanodine receptor calcium release channel activity in muscle (1,12). We hypothesized that SelM could play a role in regulating calcium release from ER calcium stores (37).…”
mentioning
confidence: 99%